Empowering elementary school teachers through early detection of visual impairment training in Makassar - Erfina, Erfina; Rahayu, Sri Bintari; Hariati, Suni; Andriani, Andriani; Basrah, Miftahul Jannah; Parawansyah, Asrul; Rahma, Nurmaulida (Community Empowerment, 2025)
Early detection of visual impairment in elementary school students is crucial for supporting academic achievement and child development. This community service activity aimed to increase the knowledge of teachers at SD Inpres Jongayya and Andi Tonro Makassar regarding the early detection of visual impairment. The method involved training and simulation on the use of the Snellen chart. Participant knowledge was evaluated using a pre-test and post-test design. The results showed an increase in teacher knowledge scores after the training, from an average pre-test score of 7.41 ± 1.570 to 7.79 ± 1.612 on the post-test. However, this increase was not statistically significant. This training provided an initial positive impact, but to ensure program sustainability, supporting efforts such as periodic supervision, provision of standard guidelines, and incentives for implementing teachers are necessary.